Hegelian Trinitarianism between Christianity and Hinduism: a new look from Saivism - Costa Lima, Danillo; Vieira Lobato, Rian (Revista Eletrônica Estudos Hegelianos, 2023)
This article aims to expose and critically evaluate the controversy launched by Hegel in his comparison of the religious representation of the Trimurti against the  Holy Trinity, from pur??ic Hinduism and Christianity respectively. The Germanic philosopher understands that the doctrine of the Trimurti cannot establish a coherent basis for a triadic conception of divinity that is truly dialectical, since the third member of the triad is reduced to a mere destroyer that in itself does not differ coordinatively in relation to the other members: that is, it does not represent a true reconciliation of the spirit as presented in the Christian trinity, but only a transition in the form of a constant cycle from creation to destruction. This failure to develop a truly dialectical divine triad would condemn Indian thought to conceiving the absolute in terms of a mere “monochromatic formalism”. Having exposed the criticism, we intend to evaluate it through the lenses of thinkers from the tradition of Siddhanta and Trika strands of Saivism, proposing that we find there Hegel's criticisms already anticipated and answered, to the point of developing a philosophical and religious conception of the triadic absolute which is profoundly similar to that of Hegel himself.
Keywords: Compared Theology; Trinity; Hegel; Saivism; India